Implementasi Pendidikan Karakter: Kepemimpinan Etis, Pengembangan Kapasitas Guru dan Budaya Sekolah - Dedi Suhardi; Dedy Achmad Kurniady; Aan Komariah; Rois Abdul Fatah (Jurnal Administrasi Pendidikan, 2021)
The purpose of this study is to analyze the role of ethical leadership, teacher capacity building and school culture in the implementation of character education. This study used a mixed method sequential expalanatory survey method of 252 private junior high schools in West Java, known as Boarding Schools, data analysis used a Co-variant-based SEM approach. The results showed that leadership in boarding school-based junior high schools was formed by the leadership's awareness of ethical values. The teacher is not yet fully ready to accept the online-based learning process and the inter-action limitation system in terms of efforts to achieve learning objectives in the learning system in the boarding school. The cultural values developed include local wisdom, orientation to science and theology. The successful implementation of character education depends on the ability, capability and contribution of the individual in providing character education. Ethical leadership, teacher capacity building and school culture have a significant role in the effectiveness of implementing character education.